2013
DOI: 10.1089/met.2012.0065
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adiponectin in Relation to Race–Ethnicity and Vascular Risk Factors in the Northern Manhattan Study

Abstract: Background: Population-based data on serum adiponectin levels, an adipocytokine secreted from adipose tissue, are lacking, particularly across race-ethnic groups. Studies have suggested an inverse association between adiponectin and vascular risk factors, but data are limited and inconsistent. We examined the cross-sectional association between adiponectin, vascular risk factors and race-ethnicity in the population-based Northern Manhattan Study (NOMAS). Methods: Blood samples, anthropomorphics, and vascular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 64 publications
3
21
0
Order By: Relevance
“…NHB youth have significantly lower adiponectin concentrations compared with their white peers irrespective of adiposity (7,8,29). Studies of HMWA reveal similar racial/ethnic contrasts in adults (21). In line with these observations, the current study showed that NHB youth with type 2 diabetes had significantly lower total adiponectin and HMWA concentrations at the time of randomization in TODAY even after adjusting for the higher BMI in NHB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NHB youth have significantly lower adiponectin concentrations compared with their white peers irrespective of adiposity (7,8,29). Studies of HMWA reveal similar racial/ethnic contrasts in adults (21). In line with these observations, the current study showed that NHB youth with type 2 diabetes had significantly lower total adiponectin and HMWA concentrations at the time of randomization in TODAY even after adjusting for the higher BMI in NHB.…”
Section: Resultsmentioning
confidence: 99%
“…To probe the metabolic/hormonal mechanism(s) potentially responsible for the racial/ethnic disparity in therapeutic failure rates in TODAY, we targeted 1 ) adiponectin because it is known to vary by race/ethnicity (79,21) and 2 ) insulin sensitivity and β-cell function because of the well-established racial/ethnic contrast (25,22). …”
Section: Resultsmentioning
confidence: 99%
“…For example, Caucasians have a higher level of adiponectin than other ethnicities such as Asians or African Americans [13,53]. In a multiethnic study, Morimoto et al reported significant ethnic differences in the level of leptin, adiponectin, IL-6 and CRP between Caucasians, Japanese Americans, Latinos, African Americans and Native Hawaiians [17].…”
Section: Discussionmentioning
confidence: 99%
“…22 The populations where adiponectin as marker were investigated were from various ethnic groups. 12,[23][24][25] There is a need to evaluate adiponectin levels in Indian population as there is limited population based evidence among Indians during the progression of normoglycemic to hyperglycemic condition. A recent study done by Mohan et al indicated profiling of serum adiponectin in healthy, IGT, and diabetic individuals.…”
Section: Discussionmentioning
confidence: 99%